Reduplikasi Bahasa Melayu Riau Dialek Kampar Kiri - Andriana, Mella; Auzar; Charlina (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2020)
This study aimed to analyze the form and meaning of reduplication in the Malay language of the Kampar Kiri dialect. This study used a qualitative approach and descriptive method which aimed to describe the form of reduplication and analyze the meaning of the Malay language of Kampar Kiri dialect. The object of this study was in the form of Riau Malay dialect Kampar Kiri dialect used by the people of Batu Sasak Village. Data was obtained by fishing techniques, interview techniques, record techniques, and note-taking techniques. The data were described based on the type and analyzed based on the meaning of the reduplication of the Malay language in the Kampar Kiri dialect. Data that has been analyzed are then formulated into conclusions. After analyzing the data, ten forms were found, namely one beinfix reduplication, three sulfimated reduplication, six prefixed reduplication in the first phallus, four had reduplication prefixed on the second phallus, and three were suffixed reduplication. In addition, six confixed reduplication, five regional reduplication, three voice copy reduplication, ten affixed duplication reduplication, and ten duplicate reduplication without affixes. The total number of forms of reduplication in Riau Malay in the Kampaar Kiri dialect were 51 one data.